112 USP18 promotes cell proliferation and suppressed apoptosis in cervical cancer cells via akt signaling pathway. (4th December 2020) - Tellydiao, Wenjing; Guo, Qisang; Zhu, Caiying; Song, Yu; Feng, Hua; Cao, Yuankui; Du, Ming; Chen, Huifen
Abstract : Introduction/Background: Cervical cancer is one of the most common malignancies in women worldwide. USP18 (USP43), a member of Ubiquitin-specific protease family, has been linked to several human malignancies except cervical cancer. The current study aimed to explore the expression and possible role in cervical cancer. Methodology: Real-time PCR and immunohistochemical staining was performed to analyze USP18 expression in cervical cancer tissues and normal tissues. USP18 expression was manipulated in cervical cancer cell lines, and its biological function in cell proliferation and apoptosis was assessed by Cell Counting Kit-8 assay and Annexin V/PI staining, respectively. Results: We demonstrated that USP18 expression was increased in cervical cancer specimens and cell lines. Knocking down of USP18 in cervical cancer cell lines, SiHa and Caski, inhibited cell proliferation, while induced apoptosis and the expression of cleaved caspase-3. On the contrary, USP18 overexpression showed reversed effects in Hela cells. Moreover, Gene Set Enrichment Analysis showed that USP18 expression level was correlated with PI3K/AKT signaling pathway in cervical cancer. Further, the PI3K/Akt inhibitor LY294002 blocked the effects of USP18 overexpression on cervical cancer cells. Conclusion: The current study indicates the oncogenic role of USP18 in cervical cancer, which will deepen the understanding in the pathogenesis of cervical cancer and may provide a novel target for cancer therapy.